Prediction of water table in an alluvial aquifer using modflow - Al-Hassoun, Saleh A.; Mohammad, Thamer Ahmed (Universiti Putra Malaysia Press, 2011)
Groundwater is the main source of water in the Kingdom of Saudi Arabia (KSA). A larger part of groundwater is founded in alluvial (unconfined) aquifers. Prediction of water table elevations in unconfined aquifers is very useful in water resources planning and management. During the last two decades, many aquifers in different regions of the KSA experienced significant groundwater decline. The declines in these aquifers raised concerns over the quantity and quality of groundwater, as well as concerns over the planning and management policies used in KSA. The main objective of this study was to predict water table fluctuations and to estimate the annual change in water table at an alluvial aquifer at wadi Hada Al Sham near Makkah, KSA. The methodology was achieved using numerical groundwater model (MODFLOW). The model was calibrated and then used to predict water table elevations due to pumping for a period of 5 years. The output of the model was found to be in agreement with the previous records. Moreover, the simulation results also show reasonable declination of water table elevations in the study area during the study period.